Investigation of the Roles of Plasma Species Generated by Surface Dielectric Barrier Discharge. Issue 1 (December 2018) - Pai, Kedar; Timmons, Chris; Roehm, Kevin; Ngo, Alvin; Narayanan, Sai; Ramachandran, Akhilesh; Jacob, Jamey; Ma, Li; Madihally, Sundararajan
Abstract As an emerging sterilization technology, cold atmospheric plasma offers a dry, non-thermal, rapid process that is minimally damaging to a majority of substrates. However, the mechanisms by which plasma interacts with living cells are poorly understood and the plasma generation apparatuses are complex and resource-intensive. In this study, the roles of reactive oxygen species (ROS), nitric oxide (NO), and charged particles (ions) produced by surface dielectric barrier discharge (SDBD) plasma on prokaryotic (Listeria monocytogenes (Gram-positive)) and eukaryotic (human umbilical vein endothelial cells (HUVEC)) cellular function were evaluated. HUVEC and bacterial oxidative stress responses, the accumulation of nitrite in aqueous media, air ion density, and bacterial inactivation at various distances from SDBD actuators were measured. SDBD actuator designs were also varied in terms of electrode number and length to evaluate the cellular effects of plasma volume and power distribution. NO and ions were found to contribute minimally to the observed cellular effects, whereas ROS were found to cause rapid bacterial inactivation, induce eukaryotic and prokaryotic oxidative stress, and result in rapid oxidation of bovine muscle tissue. The results of this study underscore the dominance of ROS as the major plasma generated species responsible for cellular effects, with ions and RNS having a secondary, complimentary role.